Optimization of the trimming tilting angle of the electric tiltrotor propeller group - V. I. Busurin; P. V. Mulin (Научный вестник МГТУ ГА)
The paper examined the possibility of improving the energy efficient performance of an electric tiltrotor with a lift-propulsion propeller group for a steady flight mode by reducing the energy consumption of the propeller group per unit of time or per unit of the path traveled by the electric tiltrotor. This is achieved by selecting the optimal tilting angles of the electric tiltrotor total thrust vector. In the proposed approach, the trimming tilting angle of the propeller group is variable, depending on the aerodynamic characteristics of the electric tiltrotor, its propeller group. Since the propeller group is equipped with the drives for tilting them, this approach is easily implemented by the conventional facilities of the electric tiltrotor. The tilting of the total thrust vector, on the one hand, leads to an increase in the effective value of the aerodynamic lift coefficient and, on the other hand, it is accompanied by a decrease in the projection of the total thrust vector on the flight speed vector, a change in the drag and power required to create the thrust of the propeller group. This circumstance makes it necessary to solve the optimization problem in order to increase the maximum endurance and long-range capabilities in the cruise mode of the electric tiltrotor flight. The paper presents a method for calculating the optimal tilting angles of the total thrust vector based on the equations of steady motion of the electric tiltrotor in the cruise flight mode, the expression for the total power required for the rotation of the propellers of the propeller group. The analytical dependences for the optimal tilting angles of the total thrust vector are obtained depending on the ratio of the wing area to the total propeller-disk area of the propeller group and the aerodynamic quality of the electric tiltrotor.